The spatial distribution and diversity of ground fern species in the buffer zone of Samar Island Natural Park (SINP), Paranas, Samar, Philippines - Salazar, Pauline C. (2022)
Samar Island Natural Park (SINP) is considered to be the most important biodiversity refuge in the island of Samar. It is home to many living organisms including ground ferns which are one of the most significant understory vegetation because of its various economic uses. This study determined the spatial distribution and diversity of ground fern species in the buffer zone of SINP Paranas. Three 100-m transect lines were established. In each transect line, eleven 5 m x 5 m quadrats were set at an interval of 10 m. Twenty-one species belonging to 17 families and 18 genera were recorded. Species richness of ground ferns in the area constitutes about 2% of the total number of fern species in the Philippines. Among the identified species, two were listed as threatened. These were Tectaria psomiocarpa which is considered endangered, and Angiopteris evecta which is considered as other threatened species. Species diversity is considered low. This may be due to the elevation of the study site and the presence of disturbance in the area. Spatial distribution of the documented ground ferns exhibited the clumped, random, and regular pattern, with the clumped pattern observed in 90% of the documented ground fern species. This high spatial aggregation pattern may be caused by both dispersal limitation and habitat preference.